2020
DOI: 10.3390/ma13153262
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plastic Waste on the Heat-Induced Spalling Performance and Mechanical Properties of High Strength Concrete

Abstract: This paper investigates a potential application of hard-to-recycle plastic waste as polymeric addition in high strength concrete, with a focus on the potential to mitigate heat-induced concrete spalling and the consequent effects on the mechanical properties. The waste corresponds to soft and hard plastic, including household polymers vastly disposed of in landfills, although technically recyclable. Mechanical and physical properties, cracking, mass loss, and the occurrence of spalling were assessed in high st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…This reaction improves the bond between constituents improving performance of the HSC resisting higher temperatures. Additionally, results presented in Figure 14 [ 5 , 68 , 77 ] show that adding metakaolin or ground pumice proved to yield the best results [ 68 ]. In fact, it could maintain at least 70% of its strength at 500 °C [ 68 ].…”
Section: Response Of Different Concrete Types Exposed To Elevated Tem...mentioning
confidence: 99%
See 3 more Smart Citations
“…This reaction improves the bond between constituents improving performance of the HSC resisting higher temperatures. Additionally, results presented in Figure 14 [ 5 , 68 , 77 ] show that adding metakaolin or ground pumice proved to yield the best results [ 68 ]. In fact, it could maintain at least 70% of its strength at 500 °C [ 68 ].…”
Section: Response Of Different Concrete Types Exposed To Elevated Tem...mentioning
confidence: 99%
“…Furthermore, High Performance Micro Concrete (HPMC) which relies only on fine aggregates could retain 30% of its tensile strength at 1000 °C after being subjected to cooling [ 67 ]. In addition, Figure 17 [ 77 ] shows the behavior of HSC after incorporating plastic waste. It was found that they could be better than using PP fibers as long as they are used as 3 kg/m 3 or 6 kg/m 3 quantities.…”
Section: Response Of Different Concrete Types Exposed To Elevated Tem...mentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, recycled plastic wastes can also improve selected properties of cement-based material, e.g. reduce its plastic shrinkage [10] or enhance the performance in fire [11] , [12] . The latter case is possible due to the decomposition of polypropylene, which is a common compound of plastic wastes, beginning around 200°C.…”
Section: Introductionmentioning
confidence: 99%